CariesCare International adapted for the pandemic in children: Caries OUT multicentre single-group interventional study protocol (2021)
Background Comprehensive caries care has shown effectiveness in controlling caries progression and improving health outcomes by controlling caries risk, preventing initial-caries lesions progression, and patient satisfaction. To date, the caries-progression control effectiveness of the patient-centred risk-based CariesCare International (CCI) system, derived from ICCMS™ for the practice (2019), remains unproven. With the onset of the COVID-19 pandemic a previously planned multi-centre RCT shifted to this “Caries OUT” study, aiming to assess in a single-intervention group in children, the caries-control effectiveness of CCI adapted for the pandemic with non-aerosols generating procedures (non-AGP) and reducing in-office time. Methods In this 1-year multi-centre single-group interventional trial the adapted-CCI effectiveness will be assessed in one single group in terms of tooth-surface level caries progression control, and secondarily, individual-level caries progression control, children’s oral-health behaviour change, parents’ and dentists’ process acceptability, and costs exploration. A sample size of 258 3–5 and 6–8 years old patients was calculated after removing half from the previous RCT, allowing for a 25% dropout, including generally health children (27 per centre). The single-group intervention will be the adapted-CCI 4D-cycle caries care, with non-AGP and reduced in-office appointments’ time. A trained examiner per centre will conduct examinations at baseline, at 5–5.5 months (3 months after basic management), 8.5 and 12 months, assessing the child’s CCI caries risk and oral-health behaviour, visually staging and assessing caries-lesions severity and activity without air-drying (ICDAS-merged Epi); fillings/sealants; missing/dental-sepsis teeth, and tooth symptoms, synthetizing together with parent and external-trained dental practitioner (DP) the patient- and tooth-surface level diagnoses and personalised care plan. DP will deliver the adapted-CCI caries care. Parents’ and dentists’ process acceptability will be assessed via Treatment-Evaluation-Inventory questionnaires, and costs in terms of number of appointments and activities. Twenty-one centres in 13 countries will participate. Discussion The results of Caries OUT adapted for the pandemic will provide clinical data that could help support shifting the caries care in children towards individualised oral-health behaviour improvement and tooth-preserving care, improving health outcomes, and explore if the caries progression can be controlled during the pandemic by conducting non-AGP and reducing in-office time.